RESEPSI JAMA’AH MASJID AL-AWWAB DESA PUNDUNG SLEMAN TERHADAP SHALAWAT NGELIK - Jumaida Aulia Abidsyah (Institut Agama Islam Negeri (IAIN) Keiri, 2020)
Shalawat Ngelik is a recitation of blessings using the rhythm of Javanese style accompanied by high-pitched voice or high intonation. This tradition existed in the village of Pundung, Sleman for approximately 50 years. In this article, the discussion was the reception or response of the people of the village of Pundung, Sleman, especially the jama’ah of AlAwwab mosque to the existence of Shalawat Ngelik. This research was a qualitative research with data collection techniques combining field research and library research. Analysis of the reception of the Jama'ah Masjid Al-Awwab in the village of Pundung, Sleman on the Shalawat Ngelik using reception typology categorized by Ahmad Rafiq, namely exegesis receptions, aesthetic receptions, and functional receptions. The indication of exegesis reception is seen in Kyai Nur Iman's understanding of Q.S. al-Ahzab [33]: 56. It is the basis idea of Shalawat Ngelik. Meanwhile, the aesthetic receptions can be seen in the recitation of Shalawat which is done by Ngelik, which is using Javanese style rhythms with a shrill voice or high intonation. It should be noted that the recitation of the Shalawat Ngelik using Javanese verse still refers to the Shalawat Barzanji. Finally, the functional reception is indicated by the influence on the attitudes and behavior of the Jama'ah Masjid Al-Awwab, Pundung, Sleman village. Among them, getting closer to Allah Swt, love more and make Rasulullah SAW as a role model, and by reading Shalawat Ngelik his heart becomes peaceful.